Particle Dynamics in a Viscous Fluid Under the Action of Acoustic Radiation Force - Hassan, Hassan K.; Ostrovsky, Lev A.; Stepanyants, Yury A. (Discontinuity, Nonlinearity, and Complexity, 2026)
Complex dynamics of small particles under the action of acoustic radiation force is considered. This work extends the previous studies of Ostrovsky & Sarvazyan (2009) and Ostrovsky (2015) in two aspects. Firstly, here the particle material can have an arbitrary compressibility and sound speed. Secondly, in addition to the viscosity effect described by the Stokes drag force, the Boussinesq–Basset drag force and the inertial force which includes added mass effect are accounted for. Although, as was assumed in the earlier publications, the latter effects are usually small, nevertheless their influence can be noticeable in specific cases considered in this paper. The control of particle motion by switching of acoustic modes is also studied for particles of different properties. Quantitative estimates are given for particles made of different materials.